Penggunaan Metode Pemberian Tugas Mencocok Gambar Buah Untuk Meningkatkan Kemampuan Motorik Halus Anak di Tk Gmim Sion Tomohon - Tumbel, Meiske Ester (Jurnal Ilmiah Wahana Pendidikan, 2023)
The problem formulation is how to use the assignment method and aims to determine the increase in children's fine motor skills through picture matching activities in children. This research uses Classroom Action Research (PTK) which seeks to examine and reflect in depth on several aspects of teaching and learning activities, namely children's participation in learning, the way the teacher conveys a lesson. The research subjects were 16 kindergarten children from group B2. Research data on fine motor skills was collected using observation techniques. Data from descriptive research and quantitative analysis methods. The research results in cycle I did not reach the standard of learning completeness, only reaching 37.5%, while in cycle II it had reached the standard of learning completeness, namely 87.5%. So it was concluded that there was an increase of 50% in improving the fine motor skills of children in group B2 in the 2017/2018 school year at GMIM Sion Tomohon Kindergarten after using picture media in matching activities